THE MUTIFACTORIAL PATTERN OF OSTEOPOROSIS: A REVIEW OF THE RESEARCHES OF THE DEPARTMENT OF THERAPY, INSTITUTE OF POSTGRADUATE EDUCATION, YAROSLAVL STATE MEDICAL UNIVERSITY - O. B. Ershova; K. Yu. Belova; Yu. V. Barysheva; O. A. Ganert; V. V. Kalugina; A. V. Nazarova; I. V. Novikova; M. A. Romanova; O. S. Sinitsyna (Научно-практическая ревматология, 2016)
Osteoporosis (OP) is one of the most common diseases and is characterized by serious clinical manifestations such as low-energy bone fractures that cause severe social consequences. In this connection, OP is now receiving much attention worldwide. In Yaroslavl, the Department of Therapy (Head, Professor N.I. Korshunov, MD), Institute of Postgraduate Education, Yaroslavl State Medical University (Chancellor, Prof. A.V. Pavlov, MD), has been intensively conducting researches into different aspects of OP for more than 20 years. The main areas of the investigations performed are the issues of the epidemiology and outcomes of osteoporotic fractures, the relationship of OP to different diseases (rheumatoid arthritis, cardiovascular diseases), as well as the specific features of the development of OP in fertile men and women and the problem of calcium and vitamin D deficiency in pregnant women.